Characterizing Nanoparticle Release Patterns of Laser Powder Bed Fusion in Metal Additive Manufacturing: First Step Towards Mitigation Measures. - Pernetti, Roberta; Galbusera, Francesco; Cattenone, Alberto; Bergamaschi, Enrico; Previtali, Barbara; Oddone, Enrico (Annals of Work Exposures & Health, 2023)
Laser Powder Bed Fusion (L-PBF) is a well-known Additive Manufacturing (AM) technology with a wide range of industrial applications. Potential occupational exposures to metal nanoparticles (NP) as by-products could occur in these processes, and no cogent occupational exposure limits are available. To contribute to this assessment, a monitoring campaign to measure the NP release pattern in two metal L-PBF facilities was carried out in two academic laboratories adopting L-PBF technology for research purposes. The monitored processes deal with two devices and three feedstock types, namely stainless steel (AISI 316L), aluminium-silicon alloy (A357) and pure copper, which are associated with different levels of industrial maturity. Prolonged environmental and personal real-time monitoring of NP concentration and size were performed, temperature and relative humidity were also measured during environmental monitoring. The measurements reveal a controlled NP release of the monitored processes, resulting in an average reduced exposure of the operators during the whole working shift, in compliance with proposed limit values (20 000 n cm−3 for density >6000 kg m−3 or 40 000 n cm−3 for density <6000 kg m−3). Nonetheless, the monitoring results show release events with an increase in NP concentration and a decrease in NP size corresponding with several actions usually performed during warm-up and cleaning, leading to exposures over 40–50 000 n cm−3 during a considerable time interval, especially during the manufacturing of pure copper powder. The results show that the actions of the operators, boundary conditions (relative humidity) and set-up of the L-PBF device have an impact on the amount of NP released and their size. Several release events (significant increase in NP concentration and decrease in NP size) are identified and associated with specific job tasks of the workers as well as building conditions. These results contribute to the definition of NP release benchmarks in AM processes and provide information to improve the operational conditions of L-PBF processes as well as safety guidelines for operators.